2015
DOI: 10.1016/j.bbmt.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Robust Vaccine Responses in Adult and Pediatric Cord Blood Transplantation Recipients Treated for Hematologic Malignancies

Abstract: As cord blood (CB) lacks memory T- and B-cells, and recent decreases in herd immunity to vaccine preventable diseases in many developed countries have been documented, vaccine responses in CB transplantation (CBT) survivors are of great interest. We analyzed vaccine responses in double-unit CBT recipients transplanted for hematologic malignancies. In 103 vaccine eligible patients, graft-versus-host disease (GVHD) most commonly precluded vaccination. Sixty-five (63%) patients (engrafting units median HLA-allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 60 publications
2
37
0
4
Order By: Relevance
“…Clinically validated measures of functional immune reconstitution are needed. All patients require post-transplant immunization with all relevant protein conjugate and live vaccines and vaccine responses in CBT recipients have been reported 100 .…”
Section: Infection Prophylaxis Monitoring and Therapymentioning
confidence: 99%
“…Clinically validated measures of functional immune reconstitution are needed. All patients require post-transplant immunization with all relevant protein conjugate and live vaccines and vaccine responses in CBT recipients have been reported 100 .…”
Section: Infection Prophylaxis Monitoring and Therapymentioning
confidence: 99%
“…Antibody titres in this population decrease over time if re-vaccination was not administered [13]. In double cord blood recipients transplanted for malignancy both children and adults developed responses to Prevnar 7 and or Prevnar 13 pneumococcal vaccines [14]. Our group has previously shown that allogeneic HSCT recipients are deficient in switched and IgM memory B cells [15] irrespective of time post-transplant.…”
Section: Discussionmentioning
confidence: 97%
“…Given the distinct characteristics of immune reconstitution following cord blood transplantation, Shah et al. retrospectively reviewed serologic responses to PCVs (either PCV7 or PCV13) in adult and pediatric recipients of umbilical cord HSCT . Serologic response (defined as a >3‐fold rise in titers against serotypes 14, 19F, and 23F) to a 3‐dose vaccine series was evaluable in 15 pediatric patients.…”
Section: Pneumococcusmentioning
confidence: 99%
“…Two studies have evaluated the response to pertussis vaccination in pediatric allo-HSCT recipients. In a study of umbilical cord HSCT recipients by Shah et al, 100% of pediatric patients demonstrated a pertussis-specific serologic response to a 2-to 3-dose series of Tdap administered a median of 17 months posttransplant 67. However, a separate study by Inaba et al suggests that this successful initial serologic response may not be long-lasting 139.…”
mentioning
confidence: 99%